Fiscal Policy and Unemployment in Ethiopia: Evidence From ARDL Model - Irge, Takele Wogari (Quantitative Economics and Management Studies, 2024)
One of the main objectives of macroeconomic and fiscal policy in Ethiopia, as in many other developed and developing nations, is to reduce unemployment. This study examines the impact of fiscal policy on unemployment in Ethiopia from 1990 to 2022. The analysis employed the ARDL Model and cointegration test. The variables analyzed include real gross domestic product (RGDP), government spending, tax income, trade openness, population growth, and the unemployment rate. A stationarity test was conducted, revealing that all variables except population growth were stationary at their first difference. The cointegration test indicated a long-term relationship among the examined variables. Additionally, the ECM results showed that government spending negatively affects unemployment, while tax income has a positive impact. The Granger causality results demonstrated a one-way relationship, with causality flowing from government spending to unemployment. This method provides evidence of a long-term relationship between the unemployment rate and factors such as government spending and tax income. The study suggests that the government should restructure its spending patterns by allocating more funds to productive expenditures and enhance its revenue generation by diversifying Ethiopia's revenue streams.